ANALYSIS OF THE CHEMICAL COMPOSITION OF DRINKING WATER AND ITS EFFECTS ON THE HUMAN BODY (KIUT Publication, 2025)
According to the World Health Organization, more than 2 billion people worldwide use contaminated drinking water sources. One of the main causes of this issue is the consumption of water without adequate purification, while another is anthropogenic factors. Industrial enterprises, mining operations, and manufacturing plants release toxic chemical substances that contaminate groundwater, rendering it unsuitable for use. As industry continues to develop, more chemical substances—such as polycyclic aromatic hydrocarbons, pharmaceuticals, and cosmetic products—that were previously not considered pollutants are being released into the environment. Some of these chemicals may pose potential risks to human health and the environment.